Evacuation of yeast and fungal cells using the Sponge-Like Protocol: A new approach for fungal control - Amro Abd Al Fattah Amara, Nawal Abd El-Baky (Journal of Applied Pharmaceutical Science, 2022)
No abstract available.
Keywords: Evacuation, yeast, fungal, Sponge